Peran Komunikasi Orang Tua Dalam Keluarga Sebagai Upaya Pencegahan Perilaku Vaping Remaja - Denny Hasbiyantoro; Sabrina Harum Kesuma; Siti Najiyah Sya’rani (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
This study highlights the crucial role of parental communication within the family in preventing vaping behavior among adolescents. In an era of rapid technological advancement, adolescents as digital natives have extensive access to information via social media, the internet, and other digital devices, all of which influence their behavioral patterns, including vaping. This phenomenon presents both health and social issues; many adolescents perceive vaping as a safer, modern alternative to conventional cigarettes, whereas, in reality, vaping carries serious health risks such as heart attacks and tissue damage that are further exacerbated by a lack of effective, open communication between parents and adolescents. This study employs a qualitative approach, utilizing literature reviews and content analysis to understand the dynamics of family communication regarding vaping prevention. The findings confirm that democratic, open, and supportive family communication patterns can foster a protective environment, strengthen adolescents' ability to resist peer pressure, and reduce the risk of engaging in vaping. Establishing effective communication to prevent vaping requires parents to employ strategies involving appropriate message formulation, consistent implementation, and ongoing evaluation.